TRANSFORMATION OF PEDAGOGICAL COMPETENCIES IN THE PROCESS OF DIGITALIZATION OF THE EDUCATIONAL ENVIRONMENT - Kaldibekov Alibek Bolatbekovich (International Journal of Literature and Language Studies, 2026)
This article provides a scientific and pedagogical analysis of transformational changes occurring in the content, structure, and functional tasks of pedagogical competencies in the process of digitalizing the educational environment. It substantiates that, in the context of a digital educational environment, the professional training of future teachers should not be limited only to traditional didactic, methodological, and communicative competencies, but should also be integrated with technological, digital-didactic, analytical, innovative, and reflective competencies. The article interprets digitalization as a factor that reorganizes the content of pedagogical activity and highlights the transformation of the teacher’s role from a traditional transmitter of knowledge into a subject who designs, manages, and analyzes the educational process and forms an individual learning trajectory based on digital resources. In addition, the didactic potential of digital learning platforms, electronic portfolios, learning analytics, interactive resources, and blended learning technologies in developing transformed pedagogical competencies among future teachers is revealed. As a result of the study, technological competence is substantiated as an integrative professional quality that unites pedagogical competencies in a digital educational environment.